Natural-Based Learning Practice at Muhammadiyah Pakel Elementary School - Dahuri Dahuri; Wantini Wantini; Mahdee Maduerawae (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2023)
Education is an important foundation in shaping future generations who are competent and have integrity. In the context of Islamic education, learning that is centered on fitrah (basic human nature) has become an important focus in developing students' potential. The purpose of this research is to describe the practice of nature-based learning at Muhammadiyah Pakel Elementary School, so that the focus of the research is in the form of planning and implementing nature-based learning. The research method used is a qualitative approach with case studies. Data was collected through participatory observation, in-depth interviews, and document analysis. Respondents in this study included school principals, teachers, and students of SD Muhammadiyah Pakel. The results of this study indicate that nature-based learning practices are implemented through extracurricular activities as well as fostering students' talents which are contained in 6 development models, namely: 1) religious values ​​and moral ethics, 2) physical and motor skills of students 3) reasoning knowledge, 4) grammar , 5) soul socially and emotionally, and 6) works of art. In practice, learning is done by making class groups of students according to the interests and talents of each student. This is done so that the child's self-potential is growing rapidly because in the learning process it refers to the child's talents and interests.